2011
DOI: 10.1108/14626001111179802
|View full text |Cite
|
Sign up to set email alerts
|

Small firm marketing: synthesising and supporting received wisdom

Abstract: PurposeIt is acknowledged that while there is a paucity of marketing research focusing on small firms relative to larger firms, a significant contribution to this field has been made in recent years. However, while such research has proved useful, it remains quite disparate, and gleaning a current understanding of how small firms market their goods and services, is difficult. This paper aims to produce an empirically validated framework of small firm marketing activities.Design/methodology/approachA qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…O'Donnell () presents an empirically derived model that captures the key activities in which small firms engage, which were found to be: marketing planning, managing limited resources, keeping existing customers, acquiring new customers, gathering information about customers, gathering information about competitors, managing the product offering, managing pricing, managing delivery; her study also highlighted and confirmed the importance of two overriding, contextual factors: industry norms and the organization's life cycle stage (O'Donnell ).…”
Section: Exploring the Concept Of Networkingmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Donnell () presents an empirically derived model that captures the key activities in which small firms engage, which were found to be: marketing planning, managing limited resources, keeping existing customers, acquiring new customers, gathering information about customers, gathering information about competitors, managing the product offering, managing pricing, managing delivery; her study also highlighted and confirmed the importance of two overriding, contextual factors: industry norms and the organization's life cycle stage (O'Donnell ).…”
Section: Exploring the Concept Of Networkingmentioning
confidence: 99%
“…However, though the application of large firm models to a small firm context is generally criticized, it is accepted that the basic principles of marketing are broadly applicable to both large and small businesses (Dragnic 2009;Reynolds 2002;Simpson et al 2006). O'Donnell (2011) presents an empirically derived model that captures the key activities in which small firms engage, which were found to be: marketing planning, managing limited resources, keeping existing customers, acquiring new customers, gathering information about customers, gathering information about competitors, managing the product offering, managing pricing, managing delivery; her study also highlighted and confirmed the importance of two overriding, contextual factors: industry norms and the organization's life cycle stage (O'Donnell 2011).…”
Section: Small Firm Marketingmentioning
confidence: 99%
“…On a more general level, the study contributes to the discussion on SME marketing practices (e.g. Gilmore et al, 2007;O'Donnell, 2011;Reijonen, 2010;Simpson and Taylor, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…). Moreover, few papers have presented a critical analysis of the background literature on SME marketing (O'Donnell ). Therefore, understanding of how the concept of marketing is seen and put into practice in SMEs is still sketchy, remaining an issue of interest among academics and practitioners (Blackburn and Kovalainen ; Reijonen ).…”
Section: Introductionmentioning
confidence: 99%